Alcohol and HIV-Derived Hepatocyte Apoptotic Bodies Induce Hepatic Stellate Cell Activation - Moses New-Aaron; Raghubendra Singh Dagur; Siva Sankar Koganti; Murali Ganesan; Weimin Wang; Edward Makarov; Mojisola Ogunnaike; Kusum K. Kharbanda; Larisa Y. Poluektova; Natalia A. Osna (Biology, 2022)
Recently, we found that both HIV and acetaldehyde, an alcohol metabolite, induce hepatocyte apoptosis, resulting in the release of large extracellular vesicles called apoptotic bodies (ABs). The engulfment of these hepatocyte ABs by hepatic stellate cells (HSC) leads to their profibrotic activation. This study aims to establish the mechanisms of HSC activation after engulfment of ABs from acetaldehyde and HIV-exposed hepatocytes (ABAGS+HIV). In vitro experiments were performed on Huh7.5-CYP (RLW) cells to generate hepatocyte ABs and LX2 cells were used as HSC. To generate ABs, RLW cells were pretreated for 24 h with acetaldehyde, then exposed overnight to HIV1ADA and to acetaldehyde for 96 h. Thereafter, ABs were isolated from cell suspension by a differential centrifugation method and incubated with LX2 cells (3:1 ratio) for profibrotic genes and protein analyses. We found that HSC internalized ABs via the tyrosine kinase receptor, Axl. While the HIV gag RNA/HIV proteins accumulated in ABs elicited no productive infection in LX2 and immune cells, they triggered ROS and IL6 generation, which, in turn, activated profibrotic genes via the JNK-ERK1/2 and JAK-STAT3 pathways. Similarly, ongoing profibrotic activation was observed in immunodeficient NSG mice fed ethanol and injected with HIV-derived RLW ABs. We conclude that HSC activation by hepatocyte ABAGS+HIV engulfment is mediated by ROS-dependent JNK-ERK1/2 and IL6 triggering of JAK-STAT3 pathways. This can partially explain the mechanisms of liver fibrosis development frequently observed among alcohol abusing PLWH.